Systematic Literature Review: Security Challenges of IoT-based Smart Home Systems - Ben-Nakhi, Abdullah Ali; Abd El-barr, Mostafa; Qureshi, Kalim Uddin (IAES Indonesian Section, 2025)
Internet of things has a wide range of applications such as healthcare, agriculture, transportation, and industrial manufacturing. Smart homes automation occupies a large segment of applications. Due to the proliferation of IoT-based smart homes systems, the attack vector on these devices expanded and became a target for attackers. Although these devices are improving constantly, security is still a challenge for them. The lack of security standardizations and hardware limitations resulted in a slow or lack of security practices in these devices. In this study, we conduct a systematic literature review to identify the exposed threats in the last five years in these devices and introduce novel countermeasures to mitigate the security issues. IEEE, ACM, Scopus, Science Direct, Springer, and MDPI databases were selected for the systematic review. The result of the systematic review were 731 articles collected. Based on reading the abstract, 605 articles were excluded, and 41 articles were excluded based on reading the full text. The result 70 articles were filtered using quality assessment criteria which resulted in 35 articles related to our search domain and answering the research questions. Additionally, a survey is conducted to elicit experts in the field knowledge to enhance our findings. We were able to identify 22 unique threats that endanger smart homes systems and the proposed countermeasures classified into 5 classes.